Pengaplikasian Maqasid al-Tasdiq Ilmu Mantik dalam Penghujahan (Burhan) Sifat Nafsiyyah: Analisis Kitab Risalah al-Tawhid: The Application of Maqasid al-Tasdiq in Mantiq within the Argumentation on Sifat Nafsiyyah: An Analysis of The Book Risalah al-Tawhid - Ali Makdom, Ahmad Hafiz; Shuhari, Mohd Hasrul; Wan Jusoh, Wan Hishamudin; Khairuddin, Wan Haslan; Ibrahim, Abdul Qahhar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This paper discusses the sifat nafsiyyah (essential attributes), one of the attributes that must be affirmed for Allah SWT, and the evidence applied based on the demonstrative principles of logic (burhan). This qualitative study employs a textual analysis method focusing on Risalah al-Tawhid by Abdul Ghani Yahya and Umar Yusuf, as well as classical works on mantiq, such as Idah al-Mubham and Hashiyah al-Bayjuri ʿala al-Sullam al-Murawnaq. The discussion focuses on a detailed explanation (tafsil) of the sifat nafsiyyah according to scholars of Ahl al-Sunnah wa al-Jamaʿah. Logical elements, particularly maqasid al-tasdiq, are applied in elaborating the burhan (demonstration) of the sifat nafsiyyah. In conclusion, the detailed evidential exposition of the sifat nafsiyyah in Risalah al-Tawhid includes elements of qiyas al-iqtirani and qiyas al-istithnaʿi or qiyas al-sharti in proving the creativeness of the universe, substances (jirm), and accidents (ʿarad).